Changing lenses to assess biodiversity: patterns of species richness in sub‐Antarctic plants and implications for global conservation. Issue 3 (1st April 2008) - Rozzi, Ricardo; Armesto, Juan J; Goffinet, Bernard; Buck, William; Massardo, Francisca; Silander, John; Arroyo, Mary TK; Russell, Shaun; Anderson, Christopher B; Cavieres, Lohengrin A; Callicott, J Baird
Abstract : Taxonomic groups and ecoregions shape the "lenses" through which biodiversity is assessed and conserved. A historical bias toward vertebrates and vascular plants in the northern hemisphere underpins how global patterns of biodiversity in terrestrial ecosystems are perceived. Here, we focus on the hitherto overlooked non‐vascular flora (liverworts and mosses) in the remote sub‐Antarctic Magellanic ecoregion of southwestern South America. We report that: (1) this ecoregion hosts outstanding non‐vascular floristic richness, with > 5% of the world's bryophytes on < 0.01 % of the Earth's land surface; (2) species richness patterns for vascular and non‐vascular plants are inverted across 25 degrees of latitude in Chile; and (3) while vascular plants are 20 times more abundant than non‐vascular plants globally and in tropical South America, non‐vascular plants are dominant in the sub‐Antarctic Magellanic ecoregion and Antarctic Peninsula. These findings have been translated into policy and conservation decisions, including the creation of the Cape Horn Biosphere Reserve in 2005 and the introduction there of "tourism with a hand lens" in the diverse "miniature forests" of bryophytes, lichens, and invertebrates. We argue for consideration of ecoregional‐ or biome‐specific indicator groups, rather than a narrow set of global indicator groups, for designing effective conservation strategies.